KEANEKARAGAMAN JENIS BURUNG PADA AREAL PERKEBUNAN KELAPA SAWIT DI KECAMATAN BESULUTU KABUPATEN KONAWE SULAWESI TENGGARA - Sitti Wirdhana Ahmad; Jamili Jamili; Mustang Mustang (University of Halu Oleo, 2016)
ABSTRACTThis research aims to know the diversity and apportionment’s of bird on oils palm plantation acreage at Besulutu area Konawe Regency South-east Sulawesi. This research was done at oils palm plantation area PT. Mega Utama Tani on September until October 2015. This research constitutes explorative research. In this research the researcher made three stations with the reason that each station has distinctive. The data of Bird was taking by use IPA (Indices Punctual Abundance method). IPA (Indices Punctual Abundance) method is bird watch method to be accounted deep given time range that at compounds by transect's method of lines Transect's line. Base on observational result, it was found as much 17 bird geneses with totaled bird individual 722 one most deep groups 7 ordo and 14 families. Shannon Wiener's diversity index I-III alternately each of 1,99, 1,96, 2,30. Bird diversity on station I and II Includes in low category, meanwhile III. Station comprises category be, apportionment Pielou's index I-III alternately each of 0,72, 0,79, 0,83. Base acquired apportionment point on three stations, the apportionment of these three stations is categorize as high.Keyword : Bird, Oil Palm Plantation, Diversity, Apportionment